Neoplasias mamárias em cães : correlação entre porte e tamanho tumoral - Stocco, Matias Bassinello (2019)
Mammary gland neoplasms in dogs are the most common, accounting for half of the visits of clinics relaying to tumors, mainly affecting senile and non-castrated dogs. At least 50% have malignant behavior and most are characterized as different patterns of carcinomas. The factors most related to the origin of these breast neoplasms are: sex, age, diet, obesity and hormone disorders. Early ovariohysterectomy, even if related to decreased incidence, is not an impediment to the occurrence of this neoplasm. Early detection of the problem is of fundamental importance for a better survival of these animals, since the risk of malignancy proportionally increases with the size of the neoplasm. Surgical intervention is the most indicated therapeutic modality and is used for the treatment of neoplasias, but protocols of multimodal therapy with the combination of surgery and chemotherapy increase the survival time of the patients. The objective of this study was to evaluate the correlation of tumor size with the different size patterns of dogs and to correlate with the patient's prognosis, as well as to determine the prevalence and information of the clinical and pathological aspects of the types and patterns of mammary gland neoplasms. The dogs of this study came from the clinical care of the University Veterinary Hospital of Cuiabá (HOVET). Dogs with previous diagnosis of breast neoformation underwent anamnesis and evaluation for tumor staging. The animals were divided according to their physical size, and submitted to total unilateral mastectomy. Tumor size was classified according to the TNM system proposed by Owen, 1980. After collection, the material was immediately referred to the Laboratory of Veterinary Pathology (LPV). After the tumors were classified, the correlation of the tumor size with the different size patterns of the dogs and correlated with the prognosis of the patient was evaluated, besides the prevalence of mammary gland tumors, their different histological types, metastases and aspects information clinical-pathological characteristics of the patients. A total of 222 animals, ranging in age from 2 to 16 years (mean of 9.51 ± 3.01 years), were the most affected, with 98.65% of the cases, only three males affected. In relation to the physical size of the 222 animals, the largest number of animals were small ones (P) with 98 small animals (P) up to 9,0kg, 60 medium animals 9,1 to 23kg (M) and 64 large animals over 23,1kg (G). There was superiority of the malignant tumors, no correlation was observed between the size of the animals with the tumor size.